Measuring satisfaction with MYIIUM student portal /cby Muna Azuddin - Muna Azuddin (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2011)
The research investigated the end-user satisfaction with student portal. The study adopted the End-User Computing Satisfaction, User Satisfaction with B2E Portal, Task-Technology Fit, Service Quality and WebQual as the theoretical basis. Target respondents were undergraduate students from three Kulliyyahs i.e. Kulliyyah of Information and Communication Technology (KICT), Kulliyyah of Islamic Revealed Knowledge and Human Sciences (KIRKHS) and Kulliyyah of Economics and Management Sciences (KENMS) at the International Islamic University Malaysia (IIUM) Gombak, Kuala Lumpur. A total of 580 questionnaires were distributed and a total number of 479 questionnaires were used for analysis. This study found that students were satisfied with the portal in terms of end-user computing and convenience of access, trust, security and privacy, consistent image and entertainment, relative advantage, task-portal fit and, entry guidance and Website structure. However, students were not satisfied with service quality, innovativeness, aesthetic design and visual appeal of the portal. This study also found that there was a significant difference in satisfaction for male and female i.e. female students are more satisfied with the IIUM Student Portal than the male students. There is no significant difference in satisfaction for ethnicity, students' academic programme and interaction effect between gender and students' academic programmes. The research implications and limitations are also discussed in the dissertation.